Linear and Nonlinear Optical Properties of Anthocyanin Dye from Red Cabbage in Different pH Solutions - Rajaa Nader; Slafa I. Ibrahim Ibrahim; Ali H. Al-Hamdani (مجلة بغداد للعلوم, 2023)
This article studied some linear and nonlinear optical characteristics of different pH solutions from anthocyanin dye extract at 180 oC from red cabbage. First, the linear spectral characteristics, including absorption and transmittance in the range 400-800 nm for anthocyanin solution 5% v/v with different pHs, were achieved utilizing a UV/VIS spectrophotometer. The experimental results reveal a shift in the absorption toward the longer wavelength direction as pH values increment. Then, the nonlinear features were measured using the Z-scan technique with a CW 532 nm laser to measure the nonlinear absorption coefficient through an open aperture. A close aperture (diameter 2 mm) calculates the nonlinear refractive index. The open Z-scan shows that as the pH increases, the sample decreases transmittance, indicative a two-photon absorption process, and the samples act as a collecting lens for the laser beam. In contrast, the results with a closed Z-scan indicate that the nonlinear absorption coefficient displays a self-focusing nonlinearity. Also, the nonlinear susceptibility decreased by increasing the value of the pH solution. Due to obvious anthocyanin dye nonlinearity dependence value on dye pH, it is possible to use the natural anthocyanin dye as a photonic device